1996
DOI: 10.1093/ije/25.2.252
|View full text |Cite
|
Sign up to set email alerts
|

The Continuing Increase in Adenocarcinoma of the Uterine Cervix: A Birth Cohort Phenomenon

Abstract: Invasive adenocarcinoma of the uterine cervix is increasing among recent birth cohorts. Analytical epidemiological studies are urgently needed to explore the risk factors responsible for the increase. The time trends for adenocarcinoma of the cervix should also be carefully monitored in the coming years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
54
3
3

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(66 citation statements)
references
References 22 publications
6
54
3
3
Order By: Relevance
“…We used the same database but extended the analysis to an additional 5 years, making short-term fluctuations in AC incidence less important. This unchanged AC incidence contrasts with the incidence rates reported from other countries where it is rising (Zheng et al, 1996;Vizcaino et al, 1998;Bergstrom et al, 1999;Plaxe and Saltzstein, 1999;Smith et al, 2000;Liu et al, 2001;Sasieni and Adams, 2001;Visioli et al, 2004;Wang et al, 2004;Bray et al, 2005). However, a stable pattern has been reported more often (Vizcaino et al, 1998;Chan et al, 2003;Bulk et al, 2005), although a decreasing incidence has also been recorded (Vizcaino et al, 1998;Bray et al, 2005;Howlett et al, 2007).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…We used the same database but extended the analysis to an additional 5 years, making short-term fluctuations in AC incidence less important. This unchanged AC incidence contrasts with the incidence rates reported from other countries where it is rising (Zheng et al, 1996;Vizcaino et al, 1998;Bergstrom et al, 1999;Plaxe and Saltzstein, 1999;Smith et al, 2000;Liu et al, 2001;Sasieni and Adams, 2001;Visioli et al, 2004;Wang et al, 2004;Bray et al, 2005). However, a stable pattern has been reported more often (Vizcaino et al, 1998;Chan et al, 2003;Bulk et al, 2005), although a decreasing incidence has also been recorded (Vizcaino et al, 1998;Bray et al, 2005;Howlett et al, 2007).…”
Section: Discussionmentioning
confidence: 57%
“…The incidences of both have increased during the last three decades, especially in women under the age of 40 years (Zheng et al, 1996;Vizcaino et al, 1998;Bergstrom et al, 1999;Plaxe and Saltzstein, 1999;Smith et al, 2000;Liu et al, 2001;Sasieni and Adams, 2001;Visioli et al, 2004;Wang et al, 2004;Bray et al, 2005). This contrasts with the decrease in squamous cell carcinoma (SCC) since the introduction of screening programmes (Bergstrom et al, 1999;Ronco et al, 2005;Kyndi et al, 2006).…”
mentioning
confidence: 99%
“…Although the human papillomavirus (HPV) is causative for both, epidemiologic studies suggest that these two histopathologic types may differ by risk factor profiles (1)(2)(3)(4)(5), patterns of detection by screening (6, 7), incidence rate trends (8)(9)(10), clinical characteristics (11), and outcomes (12)(13)(14). Therefore, to evaluate further potential etiologic differences by histopathologic type, we systematically examined incidence rate patterns for invasive squamous cell carcinomas and adenocarcinomas in the National Cancer Institute's Surveillance, Epidemiology, and End Results (SEER) program.…”
Section: Introductionmentioning
confidence: 99%
“…An increase in the absolute incidence of adenocarcinoma has been observed among workers in some countries and among some subpopulations. Smith 3 and Sasieni and Adams reported a 14-fold increase in incidence in English women born in the early 1960s compared with women born before 1935. 4 Nevertheless, Smith et al suggested the possibility of improved prognosis for patients with adenocarcinoma of the cervix in some population groups in recent years, 1,2 perhaps due to earlier disease stage at diagnosis as a result of screening; and Herbert et al demonstrated that screen-detected adenocarcinomas tended to be lower-stage malignancies compared with symptomatic adenocarcinomas, suggesting the occurrence of downstaging due to screening.…”
Section: Discussionmentioning
confidence: 99%